The Effect of Service Quality and Results on Customer Satisfaction Mudharabah Savings in PT. Bank Syariah Mandiri Gorontalo Branch Office, Indonesia - Arkani, Adelia; Muhibbuddin, Muhibbuddin (Talaa : Journal of Islamic Finance, 2021)
This research aims to determine and test the effect of service quality and profit sharing on customesrs’satisfaction of Mudharabah savings in Gorontalo branch office. This is a quantitative research. The research populations were customers at PT. Bank Syariah Mandiri Gorontalo Branch Office. The sample used in this research amounted to 90 customers. Primary datawerecollected through questionnaire whichwasthen processed using IBM SPSS 25 application. The data analysis method used simple regression analysis.The results indicate that there is positive and significant influence of service quality and profit sharing on Customers’ Satisfaction of Mudharabah savings at PT. Bank Syariah Mandiri Gorontalo Branch Office with value of 1,178 in its significance of 0.242, and the rest is affected by other factors out of this research discussion.